Isolation, characterization and optimization of keratinase production by novel strain of bacillus sp. Upmaag1 using response surface methodology - Abd Gafar, Aa’ishah (2020)
Keratinase is a type of proteolytic enzyme that is generally a serine or metalloprotease that started to gain interest due to its broad application in industry. It is generally produced as extracellular inducible enzymes using keratin as the cultivation medium. This keratin-rich material usually is produced by the poultry industry and normally discarded as wastes. As about 5-7% of the total weight of mature chickens is made of feather, an increase demand for chicken meat directly contributes to an increase in poultry waste. Therefore, it has become a challenge to manage them using required approaches that are ineffective and uneconomical and often result in serious environmental damages. Alternatively, the chicken feather can be used as a substrate for keratinase production. However, a major limitation in keratinase production is their low production level. Therefore optimisation study through statistical approach is sought to increase keratinase yield. The main objectives of this work are the optimisation of keratinase production from Bacillus sp. strain UPM-AAG1 using response surface methodology and profiling of amino acid hydrolysate produced. In this work, sixteen isolates from chicken slaughterhouse in Selangor were successfully isolated. These isolates are able to grow in a medium containing feather as the sole carbon and nitrogen. Based on the 16S rRNA gene sequence analysis, the best isolate among them were identified as Bacillus sp. UPM-AAG1. This isolate was able to produce 3.523 U/ml keratinase in 24 h at 26°C under submerged fermentation. Factors affecting keratinase activity such as pH, temperature, feather concentration and inoculum size were further optimized using Plackett Burman design (PB) and central composite design (CCD). The Placket Burman results indicate that all four factors pH, temperature, inoculum size and feather concentration were significant (P < 0.0025) and these factors were chosen for further analysis using CCD. The results show 7.5% inoculum size, 3.0% (w/v) feather concentration, pH 6.75 and temperature 30°C as the optimal keratinase production. Statistical ANOVA analysis shows that the R2 of the model was at 0.9569 and the adjusted R-Square was found to be at 0.9167 showing high correlation between the experimental designs. Using this optimised fermentation medium, keratinase activity was increased by 1.48 fold within 24 h. The amino acid analysis of the keratinase from Bacillus sp. UPM-AAG1 revealed that the prepared hydrolysate of Bacillus sp. UPMAAG1 is contain 17 different soluble amino acid including histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, valine, aspartic acid, glutamic, glycine, alanine, cysteine, tyrosine, arginine, serine and proline. In conclusion, the reliability of RSM to optimize external parameters in enhancing keratinase production from Bacillus sp. UPM-AAG1 I was demonstrated. Moreover, the successful production of amino acids was observed based on HPLC analysis of the hydrolysate of Bacillus sp. UPM-AAG1. Hence, the bacterium has a potential to be used for amino acid production from feather waste. These properties make the bacterium an excellent choice to be used for amino acid production from feather waste which can be applied to reduce poultry wastes.